Penyuluhan Fisioterapi K3 Dalam Upaya Melakukan Preventif Dan Promotive Low Back Pain Di Penjahit Sartika Express Samarinda, Kalimantan Timur - Bungan Yepinrigaseva; Siti Nur Rahimatus Shifa; Syarif Hidayatullah (Jurnal Anestesi, 2024)
Introduction: Jobs in long static positions, such as tailors, can cause musculoskeletal disorders (MSDs). MSDs are caused by unergonomic work postures, long work durations, and monotonous movements, resulting in loss of productivity and health problems. In Indonesia, the prevalence of musculoskeletal diseases is around 7.30%. Tailors often experience stiff posture and static muscle loads, causing muscle pain and stiffness in the waist and lower back. Objective: To provide preventive and promotional services and understanding of low back pain to tailors at Sartika Express, Samarinda, East Kalimantan. Method: This counseling is carried out by a health promotion method about low back pain which is carried out with presentations and using flyer media to facilitate education, this aims to understand the tailors, after that conduct a question and answer session to find out the condition and complaints of the tailors and then, educate with exercises and management that can be done independently. Conclusion: The counseling process went well, the tailors were able to follow and understand the exercises that had been taught, this activity got results in the form of understanding related to the exercises that had been taught from 0% to 100% after the counseling was carried out so that it could help the tailors prevent low back pain